The Effect of Promotional Strategies Through Social Media Marketing on Sales Volume of Micro Small and Medium Enterprises Post-Covid-19 Pandemic - Arasy Alimudin; Achmad Zakki Falani; Alexander Machicky Mayestino; Agus Sukoco; Elok Damayanti (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this study was to determine and analyze the effect of advertising promotion strategies and sales promotions through social media marketing on the sales volume of small and medium enterprises after the Covid 19 pandemic. Design/methodology/approach: This study uses quantitative research methods and includes explanatory research because this study intends to explain the causal relationship between variables through hypothesis testing using partial least squares path modeling (PLS-SEM) analysis techniques. The population is MSMEs that use promotional strategies to increase sales volume where the population size is not known with certainty, so for determining the sample using the Chocran formula and based on these calculations, in this study the number of samples used was 100 respondents. Findings: Based on the results of hypothesis testing using SEM-PLS, it is known that the effect of advertising on social media marketing has a significance of 0.04 which is smaller than 0.05. The test results of the influence of Advertising on Sales Volume show a significance scores of 0.19 which is greater than 0.05 and this is in accordance with the facts on the ground due to the COVID-19 pandemic, there is no advertising ability from MSMEs. The test results of the influence of sales promotion on social media marketing show a significance scores of 0.00 which is lower than 0.05. The test results of the influence of sales promotion on sales volume showed a significance scores of 0.00 lower than 0.05. The test results of the influence of social media marketing on sales volume show a significance scores of 0.00 which is lower than 0.05. The effect of X1 on Sales Volume (Z) through social media marketing (Y) is only 7.2%. This effect is small, positive and not significant, as well as the effect of Sales Promotion (X2) on Sales Volume (Z) through social media marketing (Y) of 13%, This effect is small, positive and insignificant. However, the total effect of X1 on Z is 0.202, which means that if X1 increases by one unit, Z can increase directly and indirectly through Y by 20.2%. This effect is Sales Volume (Z), which means that if X2 increases by one unit, Z can increase directly and indirectly through Y by 57.7%. To increase the sales volume of MSMEs after the COVID-19 pandemic, it is necessary to increase the ability of MSMEs to advertise through social media marketing without paying by creating attractive and effective sales promotion strategies in the form of news through social media which can have an impact on increasing MSME sales volume. Paper types: Research paper